Understanding of expository texts in college students: the function of previous knowledge (Revista de Psicología, 2019)
The result of text understanding depends on the linguistic properties of the speech as wellas the reader’s characteristics. The objective of this paper is to evaluate the influence ofthe previous knowledge in understanding general and specific expository texts. For it, two texts were given to novel and expert readers: one divulgation expository text and the otherone specialized expository text, by comparing the summaries of both and the answers toquestions as a measure of reading understanding. In both groups no significant differenceswere found regarding general text understanding, though a better performance of the expert group was attained regarding the disciplinarian text. Taking into account the grouping variable of subjects, these results should support the hypothesis by which prior knowledge would be the main explanatory factor regarding the yield difference between both groups.
Keywords: Text; Reading Comprehension; Knowledge; Psychilinguistics; Individualized Instruction; contextual Associations; Individual Differences.